2012
DOI: 10.1007/s11596-012-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Id1 knockdown on formation of osteolytic bone lesions by prostate cancer PC3 cells in vivo

Abstract: The formation of osteolytic bone lesions is a key process for osteolytic cancer to metastasize to the bone and is under the control of a set of transcription factors. Recently, the inhibitor of differentiation 1 (Id1) has been linked with angiogenesis, tumorigenesis, metastasis and bone formation. However, the function of Id1 during the process of bone destruction caused by cancer in vivo has not yet been elucidated. We, therefore, examined whether and how Id1 affects the ability of cancer to form osteolytic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Negative Negative Osteolytic Intratibial injection, Intrafemoral injection, intracardiac injection, Intravenous injection into human bone implanted animals Kaighn et al, 7 Nemeth et al, 5 Chu et al, 8 Wu et al, 9 Zhang et al 10…”
Section: Pc-3mentioning
confidence: 99%
“…Negative Negative Osteolytic Intratibial injection, Intrafemoral injection, intracardiac injection, Intravenous injection into human bone implanted animals Kaighn et al, 7 Nemeth et al, 5 Chu et al, 8 Wu et al, 9 Zhang et al 10…”
Section: Pc-3mentioning
confidence: 99%
“…Results from previous studies showed that one specific bone marrow stromal cell line, HS-5, secreted soluble factor(s) (HS-5 DF) that induce PCa apoptosis and neuroendocrine differentiation (NED) [8,10]. No significant effect could be seen in PC3 cell line, which primarily caused osteolytic bone lesion [8,36]. However, the phenomenon was found in an isogenic LNCaP progression model including LNCaP, C4-2, and C4-2B cell lines, which were shown to cause osteosclerotic bone lesion corresponding to PCa bone metastasis in PCa patients and animal models [8,15,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Network analysis indicates that Id1 promotes cancer morphology, cell cycle and epithelial to mesenchymal transition by influencing AP1, tnf, tgfbeta, PdgfBB and estradiol pathways [66]. Intriguingly, study also showed that Id1 could down-regulate the ability of PC3 cells to form osteolytic lesions in vivo, although in the same study it was observed that knockdown of Id1 in PC3 cells inhibited the proliferation of cancer cells in vitro [67]. While evidence also suggests that Id1 is a key factor in promoting cancer metastasis to lungs [68], the discrepancy of microenvironment in different sites may be the cause.…”
Section: Prostate Cancermentioning
confidence: 90%